Histone methyltransferase PRMT6 plays an oncogenic role of in prostate cancer - Rios, Diogo Almeida (2016)
Prostate cancer (PCa) is a major cause of morbidity and mortality. Until now the specific role of histone methyltransferases (HMTs) deregulated expression/activity in PCa is poorly understood. Herein we aimed to uncover the potential oncogenic role of PRMT6 in prostate carcinogenesis. PRMT6 overexpression was confirmed in PCa, at transcript and protein level. Stable PRMT6 knockdown in PC-3 cells attenuated malignant phenotype, increasing apoptosis and decreasing cell viability, migration and invasion. PRMT6 silencing was associated with decreased H3R2me2a levels and increased MLL and SMYD3 expression. PRMT6 silencing increased p21, p27 and CD44 and decreased MMP-9 expression and was associated with PI3K/AKT/mTOR downregulation and increased AR signaling pathway. In Sh-PRMT6 cells, AR restored expression might re-sensitized cells to androgen deprivation therapy, impacting in clinical management of castration-resistant PCa (CRPC). PRMT6 plays an oncogenic role in PCa and predicts for more clinically aggressive disease, constituting a potential target for patients with CRPC.